2020
DOI: 10.1021/acs.jpcc.0c08316
|View full text |Cite
|
Sign up to set email alerts
|

Novel p–n Heterojunction Nanocomposite: TiO2 QDs/ZnBi2O4 Photocatalyst with Considerably Enhanced Photocatalytic Activity under Visible-Light Irradiation

Abstract: The practical and widespread application of photocatalysts is limited by the problem of visible-light absorption, the immediate recombination of photogenerated electron–hole pairs, and the low number of active sites on their surface. We synthesized a series of novel TiO2 QDs/ZnBi2O4 nanocomposites through the hydrothermal method to overcome these problems. The formation of nanocomposites and their features were investigated by X-ray diffraction, Fourier transform infrared spectroscopy, energy-dispersive X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Photocatalytic degradation has been considered to be an effective and promising method for removing organic dyes from industrial wastewater, where the separation of photogenerated charge carriers and the effective absorption of dye molecules are crucial in the degradation processes . Thanks to their strong ability to capture dye molecules, high surface area, flexible skeleton structure, diversified functions, and intriguing tailorable features, metal–organic frameworks (MOFs) seem to be a promising porous photocatalyst in realizing the efficient degradation of dyes, while MOFs themselves exhibit very poor transmission/separation efficiency of photogenerated charge carriers and limited visible light adsorption ability. Consequently, several efficient inorganic semiconductor/MOF-based heterojunctions, such as TiO 2 @MOF, CdS–NRs/MOF, g-C 3 N 4 /MOF, and BiOBr/MIL-53­(Fe), were developed to significantly improve their photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic degradation has been considered to be an effective and promising method for removing organic dyes from industrial wastewater, where the separation of photogenerated charge carriers and the effective absorption of dye molecules are crucial in the degradation processes . Thanks to their strong ability to capture dye molecules, high surface area, flexible skeleton structure, diversified functions, and intriguing tailorable features, metal–organic frameworks (MOFs) seem to be a promising porous photocatalyst in realizing the efficient degradation of dyes, while MOFs themselves exhibit very poor transmission/separation efficiency of photogenerated charge carriers and limited visible light adsorption ability. Consequently, several efficient inorganic semiconductor/MOF-based heterojunctions, such as TiO 2 @MOF, CdS–NRs/MOF, g-C 3 N 4 /MOF, and BiOBr/MIL-53­(Fe), were developed to significantly improve their photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The operational procedure of the reusability test includes collection of the nanocomposite powder by centrifuge aer each catalytic experiment, washing, and drying for reusing. [47][48][49] The obtained results showed that photocatalytic nanopowder composite has high catalytic performance even aer 5 runs (see Fig. 4Sb (ESI le †)).…”
Section: Photocatalytic Evolution Of Hap/g-c 3 N 4 Nanocompositementioning
confidence: 79%
“…In particular, LaFeO 3 is known as a p-type semiconductor, while TiO 2 shows an n-type feature. 33 It is worth mentioning that the Fermi energy ( E F ) for the n-type semiconductor is ∼0.1 V below the E CB , whereas the E F is 0.1 V above the VB for the p-type semiconductor. 34 Prior to the formation of the junction, the photogenerated electrons and holes on the CB and VB of LaFeO 3 are not transferred to the TiO 2 NRs due to the unmatched position of the CB and the VB.…”
Section: Resultsmentioning
confidence: 99%